Isokinetic performance of knee flexor and extensor muscles in community-dwelling elderly women - Diogo C. Felício; Daniele S. Pereira; Bárbara Z. de Queiroz; Alexandra M. Assumpção; João M. D. Dias; Leani S. M. Pereira
AbstractIntroduction The isokinetic dynamometer enables accurate assessment of muscle function. In Brazil, few studies have assessed the isokinetic muscle performance in older adults making interpretation and comparison of results with other studies.Objectives To conduct a descriptive analysis of the performance of the muscle flexor and extensor muscles of the knee joint in elderly community and compare the performance between the age groups 65-74 years and 75 years or more.Methods This is a cross sectional observational study with a convenience sample of 229 elderly community. For the analysis of muscle performance was used isokinetic dynamometer (Biodex System 3 Pro™) in the angular velocities of 60 °/s and 180 °/s. The variables evaluated were peak torque, peak torque normalized by body weight, total work normalized by body mass, total work, average power and agonist/antagonist ratio. Descriptive analysis was used to characterize the sample. For comparison between age groups was used Student's t-test with α = 0.05.Results The elderly women with older age showed a statistically significant decrease in most of the variables (p < 0.05) except for the agonist and antagonist knee (p = 0.398).Conclusions The isokinetic was a sensitive tool to characterize the modifications caused by aging on muscle function. Elderly with results below the lower limits of the confidence intervals for all variables certainly has a decreased strength for the age group evaluated and must be addressed therapeutically. The results can be used as a benchmark in clinical practice and future research.